Screening of gingival crevicular blood glucose and capillary finger blood glucose in the diagnosis of diabetes - Alka S Waghmare; Ruhee L Chawla; B Savitha; Priyanka B Vhanmane (Wolters Kluwer Medknow Publications, 2011)
Aim: The study aimed at obtaining glucose readings using gingival crevicular blood (GCB) to screen for undiagnosed diabetes during routine dental visits. Materials and Methods: The present study included 50 patients who were divided into two groups, i.e. Group A and Group B, based on bleeding on probing at the site of collection of GCB. Group A participants had blood collected from sites having adequate bleeding on probing, whereas Group B participants had blood collected from sites with little bleeding on probing. GCB and capillary finger-stick blood (CFB] glucose readings were obtained using a self-monitoring glucometer. Statistical Analysis: Correlations between both the samples were done using Pearson's correlation. Results: Group A patients' correlations between GCB and CFB glucose readings were high, whereas in Group B patients, correlations between glucose readings were low. Conclusion: GCB can be an excellent source for screening diabetes during routine dental visits.